2019
DOI: 10.3349/ymj.2019.60.8.760
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Prevalence of Drug-Induced Parkinsonism in Korea

Abstract: Purpose Discontinuation of offending drugs can prevent drug-induced parkinsonism (DIP) before it occurs and reverse or cure it afterwards. The aim of this study was to investigate the prevalence of DIP and the utilization of offending drugs through an analysis of representative nationwide claims data. Materials and Methods We selected DIP patients of ages ranging from 40 to 100 years old with the G21.1 code from the Korean National Service Health Insurance Claims databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…This study found the incidence of DIP to have increased in older age and in women, but to have decreased overall in that period due to changes in the prescription of APs [9]. Other studies have, however, provided evidence for an overall increase in the annual prevalence of DIP; for example, from 4.09/100,000 in 2009 to 7.02/100,000 in 2015 in a South Korean study [10], which was mainly caused by the use of benzamide derivatives for gastrokinetic indications. See Table 1a,b for the relevant epidemiological studies.…”
Section: Epidemiology and Risk Factorscontrasting
confidence: 50%
See 1 more Smart Citation
“…This study found the incidence of DIP to have increased in older age and in women, but to have decreased overall in that period due to changes in the prescription of APs [9]. Other studies have, however, provided evidence for an overall increase in the annual prevalence of DIP; for example, from 4.09/100,000 in 2009 to 7.02/100,000 in 2015 in a South Korean study [10], which was mainly caused by the use of benzamide derivatives for gastrokinetic indications. See Table 1a,b for the relevant epidemiological studies.…”
Section: Epidemiology and Risk Factorscontrasting
confidence: 50%
“…See Table 1a,b for the relevant epidemiological studies. Most published studies in community or general population settings have reported DIP to be the second (or less frequently third) most common cause of parkinsonism after IPD, especially in the older population, ranging from 2% to 76% of all cases of parkinsonism [5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. However, when a large database of over 20000 cases of druginduced side-effects over a 17-year period was examined in one French study, the rate of DIP was found to be of 0.7% [26].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…All graphs of the data were generated using KaleidaGraph 4.5 (Synergy Software, Reading, PA). To further describe testing trends, the compound annual growth rate (CAGR) 23 , 24 was determined using Equation 1 below, where V f , V i , and t represent the final value (in number of claims), initial value (in number of claims), and time (in years), respectively: …”
Section: Methodsmentioning
confidence: 99%
“…The extrapyramidal manifestations caused by sulpiride include dystonia, akathisia, parkinsonism, and tremor (Eapen et al, 1993;Mauri et al, 1996;Lai et al, 2014). Recently, two big data-based studies and one meta-analysis have focused on drug-induced parkinsonism (DIP) (Martino et al, 2018;Byun et al, 2019;Kim et al, 2019). The first population-based study concluded that use of propulsives and antipsychotics including sulpiride had a significant association with the increased risk of DIP, depending on recency and cumulative dose (Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first population-based study concluded that use of propulsives and antipsychotics including sulpiride had a significant association with the increased risk of DIP, depending on recency and cumulative dose (Kim et al, 2019). Another population-based research found that annual prevalence of DIP has increased, and the usage of specific offending medications is the major cause (Byun et al, 2019). In the meta-analysis study focused on second-generation antipsychotics, the prevalence estimates are of 15.3% for acute dystonia, 16.4% for akathisia, 29.3% for parkinsonism, and 28.2% for tremor induced by sulpiride (Martino et al, 2018).…”
Section: Introductionmentioning
confidence: 99%